THE CONSTITUENT ELEMENTS STRUCTURES COVERING OF HYPERBOLIC PARABOLOID (Academic journal Industrial Machine Building Civil Engineering, 2017)
Hypar is a hyperbolic paraboloid representing translational ruled developable anti classical surface, i.e., the surface of negative Gaussian curvature. Shaping of the parabolic elements corresponds to buckling of the shell and the main tensile forces are arranged in the ascending direction of parabolas, and the main compression force - in the direction of the descending parabola. Composite materials are formed from the combination of two or more layered materials, each having very different properties. ANSYS Composite PrepPost software provides all the necessary functionality for the analysis of layered composite structures. The paper discloses a possibility of using for shell covering negative curvature. Design solutions into constituent elements structures and computations such structures are presented.
Keywords: Hypar; negative curvature; negative Gaussian curvature; ANSYS Composite PrepPost; shell; software